MANAJEMEN LABA PADA PENAVI'ARAN SAHAM PERDANA DI BURSA EFEK JAt(ARTA : ANALISIS DENGAN MODEL HEALY - Maylianawati Maylianawati; Erny Ekawati (Jurnal Riset Akuntansi dan Keuangan, 2006)
This paper examines the existence of earnings management of the IPO companies at Jakarta Stock Exchange for the periods 1995-2003. When a firru is going public, information about the firm is available in the prosrycttts. One information that become their attention is eamings informotion.Thus, managers have incentives to manage reported earningsspecifically at periods prior to IPO in order to influence marketresponse.Tests were conducted on 84lirms. The method used to exantine earnings management'are the method that developed by Healy (1985) and ' - Aharony et al (1993).The results show that these firms manage their earnings to increase reported income before and afier gotng public, specifically in the periods one year prior to going public and one year after going public.This study also finds the association between earnings management and company. size.Kqwords: Earnings management, Discretionary accruals, Company size.